Media Convergence and the Development of Interactive Broadcasting with Metaverse Technology - Ritonga, Maisaroh; Farid, Ahmad Salman; Manda, Vijaya Kittu (Feedback International Journal of Communication, 2024)
The convergence of traditional media with metaverse technology has revolutionized interactive broadcasting by blending immersive experiences with real-time interactivity. This study explores the integration of media convergence and metaverse-driven platforms, highlighting their transformative impact on audience engagement, technological innovations, and the challenges related to infrastructure, cost, and ethical considerations. A mixed-methods approach was employed, combining qualitative and quantitative research. A comprehensive literature review established the theoretical foundation, while case studies of metaverse-enabled events, such as virtual concerts and immersive news reports, provided real-world insights. Semi-structured interviews with industry professionals offered expert perspectives on adoption barriers and strategies. Quantitative metrics, including audience retention rates and interaction times, were analyzed alongside industry reports to validate findings. The findings reveal a significant increase in audience engagement, with metaverse-driven platforms achieving 150% longer interaction times and a 20% higher retention rate than traditional formats. Technological enablers, such as VR, AR, Blockchain, and AI, were identified as key drivers of this transformation, facilitating immersive storytelling, secure digital transactions, and personalized content delivery. However, challenges persist, including high infrastructure costs, regional disparities in technological access, and ethical concerns over data privacy and intellectual property disputes. Metaverse broadcasting redefines audience interaction by enabling users to participate actively in content creation and exploration.